Pemetaan Ketersebaran dan Pola Pemeliharaan Ternak Babi di Desa Marapokot - Sode, Anastasia; Jenga Lena, Fransiskus; Freadyanus Kasi, Yohanes (Jurnal Inspirasi Peternakan, 2025)
Pig farming is maintained by the Nagekeo community because they use these animals for various events such as religious ceremonies (Catholic), traditional events, and parties. The purpose of this study is to identify the distribution patterns and maintenance practices of pig farming in Marapokot Village. This research will be conducted in April-May 2025, located in Maropokot Village, Aesesa District, Nagekeo Regency. The methods used in this study include observation, interviews, and documentation. The data analysis used in this research is descriptive analysis to describe the characteristics of the respondents. The results of this study show that the majority of respondents who raise pigs are aged between 31-45 years, indicating that most pig farmers are in the productive age range. These farmers have a low level of education, with most still at the high school level or below, and age. The people of Marapokot Village raise pigs as a side business. Pig farming is still carried out traditionally on a household scale, as can be seen from the number of livestock kept, which is between 1-5 pigs. The pigs are kept near the house and are still housed in makeshift pens.